2010
DOI: 10.1080/02640414.2010.494308
|View full text |Cite
|
Sign up to set email alerts
|

Functional differences in the activity of the hamstring muscles with increasing running speed

Abstract: In this study, we examined hamstring muscle activation at different running speeds to help better understand the functional characteristics of each hamstring muscle. Eight healthy male track and field athletes (20.1 +/- 1.1 years) performed treadmill running at 50%, 75%, 85%, and 95% of their maximum velocity. Lower extremity kinematics of the hip and knee joint were calculated. The surface electromyographic activities of the biceps femoris and semitendinosus muscles were also recorded. Increasing the running … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
128
1
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 118 publications
(149 citation statements)
references
References 33 publications
11
128
1
9
Order By: Relevance
“…One study examined the EMG activation of the BF and ST muscles during treadmill sprinting at different speeds and found different characteristics of EMG activation between these two muscles within the gait cycle at near-maximum sprinting speed [16]. However, treadmill sprinting differs from overground The purpose of this study was to quantify activation of the biceps femoris (BF) and medial hamstring (MH) during overground sprinting.…”
Section: Introductionmentioning
confidence: 99%
“…One study examined the EMG activation of the BF and ST muscles during treadmill sprinting at different speeds and found different characteristics of EMG activation between these two muscles within the gait cycle at near-maximum sprinting speed [16]. However, treadmill sprinting differs from overground The purpose of this study was to quantify activation of the biceps femoris (BF) and medial hamstring (MH) during overground sprinting.…”
Section: Introductionmentioning
confidence: 99%
“…These results can be explained anatomically by the fact that in the proximal hamstring, the BFlh and ST muscles have a combined tendon origin and proximal part of their muscle (Gibbs et al 2004 ). Considering the relations between the anatomical features of the proximal hamstrings and injury location, differences in the activation patterns between the BFlh and ST muscles, which were found in our previous studies (Higashihara et al 2010 ;Higashihara et al 2013 ), might have signifi cant effects on the mechanism of hamstring strain. During sprinting at near maximum speed, a complex neuromuscular coordination pattern is accomplished according to each hamstring muscle's specifi c functional differences.…”
Section: Relation To the Location Of The Hamstring Strain Injurymentioning
confidence: 72%
“…Kyrolainen et al ( 2005 ) found that the greatest change in the BF muscle activity pattern occurred as the speed increased from that of a slow jog to the maximum and indicated that increasing the running speed effectively requires increased EMG activity in the two-joint muscles during the entire running cycle. We previously investigated activation patterns of the lateral and medial hamstring muscles during treadmill sprinting at different speeds and observed changes in activity patterns of the BFlh and ST muscles as the speed increased (Higashihara et al 2010 ). There were no signifi cant differences in the timing of peak activation of the BFlh and ST muscles at speeds below 95 % max.…”
Section: Changes In the Activity Of The Hamstring Muscles With Increamentioning
confidence: 96%
See 2 more Smart Citations